NAVIGATING GRAMMAR CHALLENGES: STUDENTS’ STRUGGLES AND PATHS TO SUCCESS - Muhammad Dzimar; Dewi Puspitasari; Ocid Abdul Rosyid (Universitas Wiralodra, 2025)
Grammar courses often pose significant challenges for undergraduate students, particularly when instructional methods fail to align with their learning needs. This study explores the real-life experiences of four students enrolled in a mandatory grammar course at UIN K.H. Abdurrahman Wahid Pekalongan (UIN Gusdur), focusing on the obstacles they encounter and their efforts to overcome them. Using a narrative inquiry approach, the research gathered data through in-depth interviews and surveys to document the students’ individual perspectives. The findings highlight several critical issues, including ambiguous teaching methods, limited vocabulary acquisition, and difficulties in applying grammatical tenses across different contexts. These challenges are compounded by a lack of sufficient support, which undermines the students’ ability to grasp essential grammatical concepts. Despite these difficulties, the students demonstrated resilience by actively seeking supplementary resources and adopting independent learning strategies. The results underline the importance of targeted pedagogical interventions to address the specific needs of grammar learners. This study concludes by emphasizing the need for educators to provide tailored support and resources while encouraging students to take an active role in their learning. By combining personalized instruction with student initiative, grammar education can become more effective and engaging for learners.